Optimizing the Role of Industrial Dispute Mediators in Handling Industrial Relations Disputes Professionally and Efficiently - Kristiani, Enny; Suparno, Suparno (Ridwan Institute, 2025)
Industrial disputes are inevitable in any workforce, and mediators play a critical role in resolving conflicts between workers and employers, ensuring fairness and peaceful resolution. However, despite their significant function, the effectiveness of industrial dispute mediators often faces challenges related to competence, independence, and institutional support. This study aims to explore how the role of mediators can be optimized to improve professionalism and efficiency in resolving industrial disputes. Utilizing a qualitative approach, including literature studies and analysis of relevant laws and regulations, the study identifies key factors affecting the mediator’s performance. It finds that strengthening mediators' capacities, enhancing their integrity, and modernizing the mediation system are essential to improving the effectiveness of dispute resolution. The implications of these findings suggest that improving mediator training, ensuring greater independence, and updating legal frameworks will create a more effective and reliable mediation process, fostering better industrial relations. This approach will not only enhance the mediator's role but also contribute to more harmonious relationships between workers and employers, benefiting both parties and society at large.